2015
DOI: 10.1038/srep16091
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal Domain Supports a Novel Function for CETPI as a New Plasma Lipopolysaccharide-Binding Protein

Abstract: Described by our group a few years ago, the cholesteryl-ester transfer protein isoform (CETPI), exclusively expressed in the small intestine and present in human plasma, lacked a functional identification for a role of physiological relevance. Now, this study introduces CETPI as a new protein with the potential capability to recognise, bind and neutralise lipopolysaccharides (LPS). Peptides derived from the C-terminal domain of CETPI showed that CETPI not only might interact with several LPS serotypes but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…However, these changes were not observed when the F 23 R variant was evaluated. Through a standardized assay developed in our group that evaluates lipid–peptide interactions ( 28 , 37 ), samples were processed through native polyacrylamide gradient gels, which evidenced the native interaction among PC vesicles with the C-terminal peptide, a condition that decreased in the F 23 R variant (Figures 5 D,E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these changes were not observed when the F 23 R variant was evaluated. Through a standardized assay developed in our group that evaluates lipid–peptide interactions ( 28 , 37 ), samples were processed through native polyacrylamide gradient gels, which evidenced the native interaction among PC vesicles with the C-terminal peptide, a condition that decreased in the F 23 R variant (Figures 5 D,E).…”
Section: Resultsmentioning
confidence: 99%
“…We established a new methodology through the use of 0.8–15% native gradient gel electrophoresis. Later, gradient gels were stained with Sudan-black and silver protocols, according to previous work ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a different set of experiments, macrophages received 10 ng/ml LMB stimuli (10 ng/ml) for 4 and 16 h, prior the addition of a gradually increasing concentration of natLDL or oxLDL. These experiments were prolonged for additional 16 h and MTT assays performed according to the protocol previously used 11 , 34 .…”
Section: Methodsmentioning
confidence: 99%
“…Localized changes in the secondary structure of proteins and peptides are believed to work as a molecular switch regulating function or, in some cases, as a trigger for misfolding. In this context, we have described these conditions by studying the cholesteryl-ester transfer protein (CETP) and a series of apolipoproteins [8][9][10][11][12][13]. In addition, other studies have reported that phosphatidylserine (PS) vesicles could increase the peptide/aggregation ratio, suggesting an electrostatic factor as a triggering condition for the induction of conformational changes [14,15].…”
Section: Introductionmentioning
confidence: 99%